2016
DOI: 10.3390/ijerph13030322
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender, Socioeconomic Status and Home Language on Primary School Children’s Reading Comprehension in KwaZulu-Natal

Abstract: The current study constituted part of a larger, longitudinal, South African-based study, namely, The Road and Aircraft Noise Exposure on Children’s Cognition and Health (RANCH—South Africa). In the context of a multicultural South Africa and varying demographic variables thereof, this study sought to investigate and describe the effects of gender, socioeconomic status and home language on primary school children’s reading comprehension in KwaZulu-Natal. In total, 834 learners across 5 public schools in the Kwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, other research has found that students from lower or higher socioeconomic backgrounds may perform differently in reading comprehension. For example, a study in South Africa (Völkel et al, 2016) found that students from lower socioeconomic backgrounds performed better in reading comprehension than those from higher backgrounds. The researchers suggested that the reason why students from lower socioeconomic backgrounds outperformed those from higher backgrounds in reading comprehension, as found in their study, may be due to a greater sense of belonging to their schools and a greater effort to improve their academic performance.…”
Section: The Discussion On Sociolinguistic Factors' Role In Reading C...mentioning
confidence: 99%
“…However, other research has found that students from lower or higher socioeconomic backgrounds may perform differently in reading comprehension. For example, a study in South Africa (Völkel et al, 2016) found that students from lower socioeconomic backgrounds performed better in reading comprehension than those from higher backgrounds. The researchers suggested that the reason why students from lower socioeconomic backgrounds outperformed those from higher backgrounds in reading comprehension, as found in their study, may be due to a greater sense of belonging to their schools and a greater effort to improve their academic performance.…”
Section: The Discussion On Sociolinguistic Factors' Role In Reading C...mentioning
confidence: 99%
“…Although gender disparities can widen over the course of education (cf. Reilly et al 2019), some studies demonstrated that these disparities narrow or even vanish with age in high school (Völkel et al 2016) and beyond (Solheim & Lundetrae 2018).…”
Section: Differences In Reading Ability By Gendermentioning
confidence: 99%
“…Since there are few and unsuitable resources available in these schools (Brink, Motolo & Henning 2021;Spaull, Pretorius & Mohohlwane 2020), teachers rely heavily on textbooks which encourages memorisation and a lack of higher-order criticality, and denies learners a safe space for debating and creativity. Despite a plethora of initiatives to introduce constructivist pedagogies, and provide all schools with a variety of resources in different languages to encourage questioning, critical thinking and mutual discovery of knowledge, the South African education system continues to experience many literacy challenges (Völkel et al 2016).…”
Section: Introductionmentioning
confidence: 99%